Economic integration of Ukraine and eu countries in the context of creation global and regional value chains - Berenda, S.V.; Zelzer, I.I. (V.N.Karazin Kharkiv National University, 2016)
Abstract. The article investigates the economic integration of Ukraine with the European Union and the potential formation of value chains. The article also analyzes trilateral foreign trade of Ukraine, the EU and Russia; the basic components of its structures. The analysis of foreign trade relations was performed with the matrix method, trade flows were analyzed based on Intra-Industry Trade and Inter-Industry Trade. The level of economic integration, and therefore the quality of economic integration in terms of theoretical principles and practice of international trade were estimated with the help of the Grubel-Lloyd index. It showed that participation of Ukrainian companies in the European value chains remains is low.
ГОСПОДАРСЬКА ІНТЕГРАЦІЇ УКРАЇНИ З КРАЇНАМИ ЄС В КОНТЕКСТІ УТВОРЕННЯ ГЛОБАЛЬНИХ ТА РЕГІОНАЛЬНИХ ЛАНЦЮГІВ ДОДАНОЇ ВАРТОСТІ
Keywords: Key words: foreign trade of Ukraine, the EU, Grubel-Lloyd index, international cooperation, economic integration, value-added chains.; Research Subject Categories::SOCIAL SCIENCES